2010
DOI: 10.1039/c0cc01381a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient chemoenzymatic synthesis of β1–4-linked galactosides with promiscuous bacterial β1–4-galactosyltransferases

Abstract: An efficient one-pot multienzyme approach has been developed for the synthesis of structural diverse LacNAc, lactose, and their derivatives including those containing negatively charged 6-O-sulfated GlcNAc and C2-substituted GlcNAc or Glc analogs. Two bacterial β1–4-galactosyltransferases, NmLgtB and Hp1–4GalT, exhibits promiscuous and complementary acceptor substrate specificity. The application of these enzymes in the one-pot multienzyme system allows the access to complex disaccharides with diverse structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
190
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(207 citation statements)
references
References 41 publications
5
190
0
2
Order By: Relevance
“…Andreana et al, 2002) for the formation of novel monosaccharides,643 but commonly available sugars may also be chemically modified 644(Cai et al, 2009a,b;Lau et al, 2010). Activation of these sugars 645 is achieved by coupling with promiscuous (anomeric) kinases and 646 uridylyltransferases to yield the corresponding UDP-sugars(Fig.…”
mentioning
confidence: 97%
“…Andreana et al, 2002) for the formation of novel monosaccharides,643 but commonly available sugars may also be chemically modified 644(Cai et al, 2009a,b;Lau et al, 2010). Activation of these sugars 645 is achieved by coupling with promiscuous (anomeric) kinases and 646 uridylyltransferases to yield the corresponding UDP-sugars(Fig.…”
mentioning
confidence: 97%
“…In another piece of work reported by Chen and co-workers, two bacterial β-1,4-galactosytransferases, NmLgtB and Hp1-4GalT, showed promiscuous and complementary specificity for GlcNAc monosaccharide substrates with 6-O-sulfation or N-sulfation [84]. Using these enzymes in the one-pot multienzyme synthesis efficiently generated an array of LacNAc and lactose derivatives [84].…”
Section: Chemoenzymatic Synthesismentioning
confidence: 96%
“…Using these enzymes in the one-pot multienzyme synthesis efficiently generated an array of LacNAc and lactose derivatives [84]. Moreover, chemoenzymatic synthesis of sulfur-linked saccharides was also investigated [85].…”
Section: Chemoenzymatic Synthesismentioning
confidence: 99%
“…Although the expression of mammalian GalTs by E. coli has been reported, these attempts have mainly produced insoluble forms of the enzymes that were difficult to reactivate in large amounts; however, in comparison to mammalian b-1,4-GalTs, bacterial GalTs have the advantage of easy production in E. coli and better tolerance to substrate modification. [24] Previous studies have shown that b-1,4-GalT from Neisseria meningitides loses its activity when a histidine tag is fused to either its N-or C-terminus. [25] To facilitate the purification step of the GalT in this study, the b-1,4-GalT gene (lgtB) was cloned and then overexpressed in E. coli by an intein-mediated protein purification system.…”
Section: Expression and Purification Of The Recombinant Enzyme (Galt)mentioning
confidence: 99%